Tiger Rag as performed by the Quintet of the Hot Club of France: history, analysis and performance practices (Per Musi, 2011)
Study about the assimilation of jazz into French popular culture of the 1930s and the emergence of a society of jazz enthusiasts, especially around Le Quintette du Hot Club de France. The transcription and analysis of Tiger Rag, composed by the members of the Original Dixieland Jazz Band (Nick La Rocca, Eddie Edwards, Tony Sbarbaro, Larry Shields and Harry da Costa) and performed by Le Quintette reveal performance practices of its main soloists: Django Reinhardt on the guitar and Stephane Grappelli on the violin.